ANALISIS CLASH AVOIDANCE DENGAN BIM PADA RENCANA STRUKTUR OVERPASS - Hendri Wicaksono; Nunung Martina (Politeknik Negeri Jakarta, 2026)
Analysis of clash avoidance with BIM on the overpass structure plan of the Double - Double track (DDT) Package A Phase II Manggarai - Jatinegara development project was chosen because it is vulnerable to clashes. This study aims to obtain the results of the analysis of clash avoidance on the work plan of the overpass structure and obtain the perception of BIM users in the application of clash avoidance on the overpass structure. Interference check is used in conducting clash avoidance analysis and interviews with purposive sampling technique chosen to obtain the perception of BIM users in the application of clash avoidance. The results of this study found that there was a time clash between 1 P12B and P13B point Bored Pile structure plans as well as 12 P12B bored pile structures and 6 P13B bored pile structures with SO6 track plans. From the results of the interference check report, it is then used as an evaluation of contractors, consultants, and service users in making changes to the structural work plan. According to the perception of BIM users, it is found that clash avoidance on the overpass structure is very important, but with attention to the accuracy of 3D BIM modeling. The accuracy of 3D BIM modeling can be achieved by connecting AutoCAD Civil 3D and Revit and data collection. In using the interference check feature, you can find out the clash as early as possible, but it requires hardware specifications that support the process.